La finanza come volano per la crescita aziendale - il caso “Piquadro” - Palazzi, Federica (Piccola Impresa / Small Business, 2010)
Abstract The “Piquadro” case study shows the existing relation between the fast firm growth and the financing policies adopted, consistently with decision maker’s objectives. The Piquadro Group, born in 1987, realized a successful rapid development since 1998, reaching the medium size. The international quantitative and qualitative development strategies joined effectively together. The entrepreneurial group used awareness corporate finance as basic tool for firm growth. The traditional financing tools (self-financing, commercial debts) have been combined with more developed financing tools (like private equity operator support or stock exchange quotation), realizing an equilibrated capital structure and keeping unchanged family character of the Piquadro Group.